Representações sociais sobre o corpo construídas por pessoas idosas - Veloso, Laura de Sousa Gomes (2022)
The body and aging, from the perspective of symbolic constructions, are under the influence of thought and behavior models in a sociocultural environment. This conception can give the body the ability to be a product and promoter of knowledge in which the body and aging are important objects to be studied, as they enable the apprehension of everyday knowledge about the biopsychosocial transformations to which they are exposed over time. The present study aims to: (a) analyze the social representations made by elderly people about the body; (b) identify the impact of morphofunctional changes in aging, in terms of social representations about the body; (c) to investigate the influence of social representations on the body in the adoption of health care practices among the elderly. This is an exploratory study, with a qualitative approach, based on the theoretical contribution of the Theory of Social Representations. The study was carried out at the Instituto Paraibano de Avelhecimento (IPE/PB), based on Campus I of the Federal University of Paraíba. Twenty-seven elderly people of both sexes participated in the research, participants of the therapeutic workshops remotely offered by the institute, during the period from August to December 2021. The study was registered in Plataforma Brasil under CAAE nº 46069021.5.0000.5188, with approval by the Research Ethics Committee of the Health Sciences Center, through opinion No. 4,736,288, on May 26, 2021. In compliance with the sanitary measures adopted for the prevention of COVID-19, all collection procedures Data collection took place in a virtual environment, using the Google Meet® communication platform. For data collection, an in-depth interview was used, guided by a semi-structured script. The collected data were processed using the Software Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires (IraMuTeQ), version 0.7 alpha, using the Descending Hierarchical Classification (CHD) or Reinert method, and the Similitude Analysis. The results were interpreted from the theoretical framework of social representations and presented in the format of three articles, one of which was a literature review article and two original articles, namely: Article 1 - Body perception of elderly people: a scope review; Article 2 - Body and aging: a study of social representations; Article 3 - Social representations of body care. The recognition of the social representations about the body from the perspective of aging favored the interpretation of the attitudes and values of elderly people about their own age and about the old age of others. Such interpretation was externalized by the daily actions of preservation and care in relation to the body, ranging from adoption of healthy lifestyle habits to interventions that manipulate brands promoted by time. The present study also recognizes that the body and aging are configured as objects of diverse and interconnected meanings, socially shared by the elderly in their belonging groups responsible for the different ways of representing the body according to their social insertions. These results may favor a better orientation for the practices of nurses and other health professionals, observing the ability of the elderly population to face adversities, which reflects the beliefs and values learned throughout the life cycle.